A Common Thread for Adaptive Management Planning of Small-scale Fishermen Needs versus Government Policy in South Papua, Indonesia - Ivonne Raystika Gretha Kaya; Sajriawati (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Indonesian government has established measurable fishing regulations by Government Regulation 11/2023 to protect and sustain fishery resources. This policy is unsuitable for small fishermen’s needs and has resulted in mass demonstrations in South Papua. Data were conducted with the fishermen demonstrators (n=100) by participation observation, in-depth and semi-structured interviews. The results showed fishermen refused the regulated fishing regulations for vessels <30 GT as far as 12 miles, simplify the licensing process, increase the fuel quota and repeal mooring requirements only at the Merauke fishing port. Formulating laws and regulations for fisheries management requires a combination of ecological, economic, and sociocultural principles to sustain fisheries systems. Stakeholder involvement must be implemented into every policy design and decision-making stage by integrating fishermen’s perspectives in the fishing business. Integrating fishermen’s points of view can be a benchmark for the suitability of fishermen needs and sustainability of fisheries resources in each region.